2008
DOI: 10.1016/j.str.2008.05.001
|View full text |Cite
|
Sign up to set email alerts
|

A Specific Cholesterol Binding Site Is Established by the 2.8 Å Structure of the Human β2-Adrenergic Receptor

Abstract: The role of cholesterol in eukaryotic membrane protein function has been attributed primarily to an influence on membrane fluidity and curvature. We present the 2.8 A resolution crystal structure of a thermally stabilized human beta(2)-adrenergic receptor bound to cholesterol and the partial inverse agonist timolol. The receptors pack as monomers in an antiparallel association with two distinct cholesterol molecules bound per receptor, but not in the packing interface, thereby indicating a structurally relevan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

49
1,036
3
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 894 publications
(1,113 citation statements)
references
References 39 publications
49
1,036
3
2
Order By: Relevance
“…2F), our model identifies residues 196-200 and 295-305 which are located near residues 203, 204, 207, 293, 308, and 312, which in turn are known to be involved in ligand binding (41,42,49). Residues 136-140 are in close spatial proximity to the DRY motif (residues 130-132), and residues 226-230 are located near the assumed β-arrestin binding site (40).…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…2F), our model identifies residues 196-200 and 295-305 which are located near residues 203, 204, 207, 293, 308, and 312, which in turn are known to be involved in ligand binding (41,42,49). Residues 136-140 are in close spatial proximity to the DRY motif (residues 130-132), and residues 226-230 are located near the assumed β-arrestin binding site (40).…”
Section: Resultsmentioning
confidence: 96%
“…Residues 136-140 are in close spatial proximity to the DRY motif (residues 130-132), and residues 226-230 are located near the assumed β-arrestin binding site (40). Interestingly, the allosteric coupling map also identifies residues 62-66, 148-152, and 335-340, which are located near residues 70, 147-151, 154, 158, and 341 which may be involved in cholesterol binding (49). Residues 95-99 and 178-183, which form solvated loops, may interact with allosteric modulators.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…For example, cholesterol modulates agonist binding to oxytocin receptors (Gimpl and Fahrenholz, 2002), 5-HT receptors (Pucadyil and Chattopadhyay, 2004) and μ-opioid receptors (Qiu et al, 2011), whereas other GPCRs are less influenced (Oates and Watts, 2011). Stability studies have demonstrated the binding of cholesterol molecules to a conserved motif located between helices 1-4 (Hanson et al, 2008). Recently, relevant phospholipids were found to affect GPCR function.…”
Section: Rm and Hmnsmentioning
confidence: 99%
“…T he recent crystal structures of the ␤ 2 -adrenergic receptor (␤ 2 AR) represented a significant advance in the study of G protein-coupled receptors (GPCRs) (1)(2)(3)(4), which constitute the largest class of both human membrane proteins and drug targets (5). ␤ 2 AR, an important target for cardiac and asthma drugs, has long served as the prototypical ligand-binding GPCR and has been extensively characterized in experimental work over several decades (6).…”
mentioning
confidence: 99%